TEKNOGOGI: Model Pembelajaran Baru dan Masyarakat Kota - Elia Tambunan (UKI Press, 2020)
Not a few teachers in Indonesia, despite being technology users, are not yet good at using it as technogogy. As a result of the teacher’s habit of using the classroom as a place of learning in formal schools, they encounter serious obstacles in the online learning system, especially those who are no longer young. Technology, teachers, society, and online learning, as material objects for discussion in this paper, have a problematic relationship. This paper intends to describe the practical use of technology as a fun learning devices for urban society in Indonesia, namely technogogy with Salatiga as an example. With qualitative data collected through participant observation of 29 teachers as a research method between March and September 2020 and then analyzed, researchers found interesting empirical data. The COVID-19 pandemic has corrected the performance of teachers who are accustomed to vocalizing. Online systems require the latest digital-based technology literacy levels to ensure learning systems are not just administrative jobs for teachers. Living Books produced by Jungle School function as a technology containing transformative thematic instruction that can fulfill learning modalities for students from various countries. It is a novelty of urban education praxis, shown by this paper, a new learning technology that can also be adopted and innovated by practitioners of further Christian Religious Education.